A Method for Economical Smartphone‐Based Clinical 3D Facial Scanning. Issue 9 (12th November 2020) - Nightingale, Renee Christine; Ross, Maureen Therese; Allenby, Mark Colin; Woodruff, Maria Ann; Powell, Sean Keiran
Abstract: Purpose: Three‐dimensional (3D) facial scanning is an emerging clinical tool to capture external anatomical features for quantitative assessment and treatment in a wide range of clinical settings. Materials and Methods: In this study, an economical approach for rapid scanning of faces in the clinic was developed and validated to record valuable 3D patient data using smartphone cameras and photogrammetry software. Five novice operators were recruited to watch an instructional video developed on the technique before scanning 20 healthy adult participants. Results: The smartphone‐based photogrammetry approach produced scans with 1.3 mm (±0.3 mm) accuracy in comparison to a metrology‐rated gold standard device and were 88% (±14%) complete, with no significant difference observed between operators. A moderate to strong intrarater reliability was determined for all novice operators, suggesting that first‐use operators can capture consistent scans based on watching an instructional video. Conclusion: Smartphone photogrammetry could provide a rapid, noninvasive and economical method to capture patient morphological data for clinical assessment and personalized device manufacture. Inexperienced operators can quickly learn and utilize smartphone photogrammetry to provide accurate and reliable facial scans, essential for future clinical translation.